2022
DOI: 10.3389/fnut.2022.960218
|View full text |Cite
|
Sign up to set email alerts
|

Taste peptides derived from Stropharia rugosoannulata fermentation mycelium and molecular docking to the taste receptor T1R1/T1R3

Abstract: This study identified the peptides in the fermentation mycelia of Stropharia rugosoannulata. The molecular weight of the peptides was below 3,000 Da. Heptapeptides to decapeptides were the main peptides in the fermentation mycelia of S. rugosoannulata. More than 50% of the peptides had salty and umami taste characteristics, and the long-chain peptides (decapeptides to 24 peptides) also played an essential role in the pleasant taste characteristics of mycelium. In the salty and umami peptide of S. rugosoannulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The T1R1/T1R3 receptor model constructed by our team was used [13] . The receptor binding cavity and binding site are the same as those in the report [35] . The molecular docking technique simulated the binding state between the umami peptides of S.rugosoannulata and the receptor protein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The T1R1/T1R3 receptor model constructed by our team was used [13] . The receptor binding cavity and binding site are the same as those in the report [35] . The molecular docking technique simulated the binding state between the umami peptides of S.rugosoannulata and the receptor protein.…”
Section: Methodsmentioning
confidence: 99%
“…Stropharia rugosoannulata , also known as the red pine mushroom, is rich in umami peptides and is a high-quality raw material for developing a base material of natural flavors [13] , [35] . Our previous research found that the base material of S.rugosoannulata prepared by traditional enzymatic hydrolysis had a high proportion of peptide (461.31 mg/g dry weight) and the flavor characteristics of the base material were close to those of the umami reference (MSG) with the same concentration.…”
Section: Introductionmentioning
confidence: 99%
“…S. rugoso-annulata mushrooms are a premium source of umami peptides. Free peptides in the fruiting body of S. rugoso-annulata reach a content of 11.28–12.56% [ 73 ]. As shown in Table 5 , the taste peptides of S. rugoso-annulata exhibit a strong umami taste, accompanied by saltiness, bitterness, richness, or aftertaste [ 5 , 74 , 75 ].…”
Section: Flavor Components Of S Rugoso-annulatamentioning
confidence: 99%
“…Free peptides in the fruiting body of S. rugoso-annulata reach a content of 11.28–12.56% [ 73 ]. As shown in Table 5 , the taste peptides of S. rugoso-annulata exhibit a strong umami taste, accompanied by saltiness, bitterness, richness, or aftertaste [ 5 , 74 , 75 ]. The taste peptides in the mature fruiting body are pentapeptides to undecapeptides and the taste threshold is relatively low (0.117–0.640 mmol·L −1 ) [ 5 , 74 ], while the peptide variety in the mycelium is particularly rich and the taste peptides are mostly heptapeptides to decapeptides [ 74 ].…”
Section: Flavor Components Of S Rugoso-annulatamentioning
confidence: 99%
“…At a mass concentration of 1 mg mL −1 , the peptide matrix had a salty evaluation value of 23.33 ± 0.11, an umami evaluation value of 13.17 ± 0.16, and a 50% ACE inhibitory concentration (IC 50 ) of 0.122 mg mL −1 , ABTS-free radical scavenging rate (%) was 72.24 ± 1.52, and a 50% DPP-IV inhibitory concentration of 6.62 mg mL −1 . [4][5][6] The ACE inhibitory activity of the S. rugosoannulata peptide matrix is more prominent than its antioxidant and DPP-IV inhibitory activity. Many ACE inhibitors have been identified from plant and animal protein hydrolysates and showed better ACE inhibitory effects in cellular models and blood pressure-lowering activity in animal models.…”
Section: Introductionmentioning
confidence: 99%